CP-120 Do educational meetings and group detailing change adherence to drug formularies in hospitals? A cluster randomised controlled trial. (24th February 2014) - Plet, HT; Kjeldsen, LJ; Christensen, RD; Nielsen, GS; Hallas, J
Abstract : Background: Lack of adherence to guidelines may lead to irrational drug use. Treatment guidelines combined with a drug formulary can assist physicians in appropriate prescribing. However, it is a challenge to implement guidelines into clinical practice. Studies have shown that multifaceted interventions are needed to successfully improve adherence to guidelines. Purpose: To examine whether educational meetings and group detailing could increase the use of drugs from the ward lists or the drug formulary in hospitals. Materials and methods: Twelve medical wards from two hospitals were randomised into three groups: control, basic and extended intervention. All wards had a ward list review before interventions. The basic intervention consisted of an educational meeting, and the extended intervention included two group detailing sessions. The proportion of drugs used from the ward list or hospital drug formulary HDF was the primary outcome. Data (DDDs, numbers and cost (Euro)) on drugs sold to the wards were retrieved from the two hospitals from 1 st July 2011 to 31 st August 2012. Baseline data: from Jul to Sep 2011, and follow-up data: from Jun to Aug 2012. Results: The proportion of formulary drugs used increased for the extended intervention group (0.04 range -0.02 to 0.09) and basic intervention group (0.03 range -0.03 to 0.09) in comparison with a decrease in the control group (-0.01 range -0.03 to -0.02). The interventions did not significantly change odds for selecting drugs from the formulary in comparison with the control group (basic intervention: OR 1.09 (95% CI 0.81 to 1.46); extended intervention: OR 1.00 (95% CI 0.75 to 1.35)). Conclusions: In this study, educational meetings and group detailing did not significantly improve adherence to ward lists or HDF. The adherence to the formularies at baseline was relatively high, which may explain why the interventions did not have a significant effect. No conflict of interest.